Analysis of Return on Assets, Debt to Equity Ratio, Company Size and Investment Opportunity Set on Share Prices in the Cigarette Sub Sector listed on the Indonesian Stock Exchange - Rimawan, M.; Muniarty, Puji (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
The purpose of this study was to determine Analysis of Return on Assets, Debt to Equity Ratio, Company Size and Investment Opportunity Set on Share Prices in the Cigarette Sub Sector listed on the Indonesia Stock Exchange. The research design used is quantitative research. The data used is secondary data in the form of time series data. Data analysis used SPSS versio 26. The research results show that: 1). Return on Asset has a significant effect on Share Price; 2). Debt to Equity Ratio has no significant effect Share Prices; 3) company size has a significant effect on Share Prices; 4). Investment Opportunity Set has no a significant effect on Share Prices; 5). And Simultan has a Significant Share Price in the Cigarette Sub Sector listed on the Indonesia Stock Exchange